Fraud Crime through Electronic System Based on Indonesian Positive Law (Decision Study No: 1356/PID/B/2016/PN.BDG) - Vinshen Saputra; Hery Firmansyah (CV. Rayyan Dwi Bharata, 2023)
Today's criminal acts of fraud continue to develop following the development of existing technology, existing legal regulations function to overcome this, but existing regulations cannot reduce these crimes but increase them. This study aims to find out how existing law enforcement is against criminal acts of fraud through electronic systems, knowing various kinds of inhibiting factors in enforcing criminal law against a crime of fraud. This research was carried out using normative juridical methods through library research by examining secondary data including regulations legislation, research results, scientific journals and references. The results of the study provide an illustration, where criminal acts of fraud through electronic systems are in principle the same as fraud in conventional ways, but the difference lies in the evidence or means of action, namely using electronic systems (computers, internet, telecommunication devices), because that is law enforcement. Fraud crimes can still be overcome by Article 378 of the Criminal Code concerning fraud and Article 28 Paragraph (1) of the ITE Law concerning Information and Electronic Transactions Furthermore, obstacles in law enforcement against criminal acts of fraud based on electronic transactions are still influenced by five factors, namely legal factors, law enforcement factors , factors of facilities or facilities that support law enforcement, social factors and cultural factors.